Examining the Impact of Renewable Energy on the Economy Using the ARDL Method - Ziya, Amin; Sotoudenia Karani, Salman (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: With the continual increase in the global population and the limited availability of energy resources, energy consumption has become a concern for all countries. Today, renewable energies have made it possible to utilize all natural potentials for energy production. However, a comprehensive examination in this field must be conducted to meet the country's energy needs and identify all areas for exploiting renewable energies. Subsequently, the creation of infrastructure and suitable environments for the exploitation, development, and provision of energy becomes significantly important. The results indicate that there is an asymmetric relationship between economic growth, energy consumption, and financial development, such that in the long and short term, a positive shock in energy consumption and financial development has led to a decrease in economic growth. The positive shock in energy consumption shows that producers' efforts to reduce energy consumption cause a reduction in economic growth in the short term.Methodology: This research investigates the impact of renewable energies on the economy using the ARDL method.Findings: The first objective of this issue is to minimize the construction costs of regional warehouses in Tehran under various scenarios, and the second objective is to minimize the costs of supply, maintenance of goods in regional warehouses; minimize the costs of sending and maintaining goods in the central warehouse; minimize the costs related to sending goods to demand points, and minimize the costs related to leftover goods in each region at the end of each period.Conclusion: The results show that the designed model optimizes the logistics costs of relief and rescue.